Bacterial Community Diversity, Richness, and Possible Immunotherapies Association in Response to Spray-Dried Porcine Plasma-Fed Diet: An Animal Model - Alina, Pirmatova; Qasim, Imad Ghanem; Mohammed, Sura Akram; Mohammed, Samer Shukur; Nassar, Waleed; Nazir, Nazarzoda Khusin (Trends in Immunotherapy, 2025)
This study aims to demonstrate the significance of employing non-invasive dietary intervention to control the diversity and abundance of bacterial communities in feces. The indexing databases Scopus, PubMed/Medline, ISI Web of Science, Embase, Cochrane Central, and CINAHL were extensively searched. Only 13 of 541 papers found in the initial searches met the criteria. Seven studies involving 210 animals were included in this meta-analysis. The SDPP group showed statistically lower Shannon (SMD: 1.20, 95% CI: 0.22–2.19, I2: 88%, p = 0.02) and Chao1 (SMD: 2.95, 95% CI: 1.99–3.91, I2: 77%, p < 0.00001) indices than the control group. The SDPP-diet fed group showed notably lower OTU counts compared to the control group (SMD: 2.99, 95% CI: 0.67–5.32, I2: 97%, p = 0.01). The Firmicutes/Bacteroidetes ratio is reliably increased following the SDPP-fed diet (SMD: 0.68, 95% CI: 0.13–1.23, I2: 0%, p = 0.02). While noticeable differences existed between studies and difficulties were encountered in replicating basic ecological measurements, the purpose of this analysis was to identify the consistent characteristics of the gut microbiota’s response to the SDPP diet, thereby pinpointing specific areas for further mechanistic research.